Transmedia Cultural Exchange and Social Identity Formation: Educational Implications of Chinese-language Films in Singapore - Wang, Jinxiu; Cui, Yanling; Sun, Peng (European Journal of Social Science Education and Research, 2026)
Transmedia storytelling is an effective means of cultural exchange in the era of globalization and digital convergence. This paper examines the role of Chinese-language movies in promoting cultural exchange among the Chinese in Singapore and the ways in which viewers access these movies through different digital platforms. The study explores the ways in which social media, television, cinema, and online forums are used as cultural interpretation spaces and community discourse through the analysis of user comments and interactions on these platforms. The research was based on a quantitative method, where 512 participants were surveyed online, and Structural Equation Modeling (SEM) and Confirmatory Factor Analysis (CFA) were used to determine the most important variables that determine transmedia engagement. The results indicate that emotional connection, cultural familiarity, and social interaction are important to improve engagement and strengthen cultural identity. The findings highlight the importance of Chinese-language films as a transmedia tool through which the diasporic communities can preserve their culture. The study can be of great use to media producers, educators, and policymakers who want to promote cross-cultural understanding.